Influence of inclination angle on buoyancy-driven convection in triangular enclosure filled with a fluid-saturated porous medium - Varol, Yasin; Öztop, Hakan Fehmi; Pop, Ioan (Springer, 2008)
The present investigation deals with the numerical analysis of steady-state laminar buoyancy-driven convection in an inclined triangular enclosure filled with fluid saturated porous media using the Darcy law equation. One wall of the enclosure is isothermally heated and the other is cooled, while the remaining wall is adiabatic. The effect of inclination angle on natural convection is investigated by varying the angle of inclination (phi) between 0 degrees and 360 degrees. The governing transformed equations are solved numerically using a finite-difference method. Obtained results are shown in the form of streamlines, isotherms, mean Nusselt numbers and dimensionless stream function for different values of the Rayleigh number Ra in the range 100 <= Ra <= 1,000. It is found that the values of the maximum and minimum mean Nusselt number are reached for phi = 330 degrees and phi = 210 degrees, respectively. However, the lowest flow strength is formed at phi = 240 degrees for all values of Ra.
Keywords: Laminar Natural-Convection; Cross-Section; Flow; Roof